SISTEM INFORMASI REKOMENDASI PRODUK PADA WEBSITE ECOMMERCE DENGAN MENGGUNAKAN ALGORITMA APRIORI - Sadar Putra Sadeli; Ari Purno Wahyu Wibowo (Jurnal Darma Agung, 2022)
The current e-commerce sales system makes it easier for someone to open a business place or shop without having to need a lot of places with even more catalogs of goods. The problem faced today is if the catalog of goods sold is very large and it is very difficult to determine the number of items that are most sold and the categories of favorite products, then an e-commerce system is created using an a priori algorithm that can determine the most categories of goods. sold by determining the number of rules or data for each transaction, this system can also read purchase patterns made by consumers so that each consumer's purchase data can be read and will later be used to determine product promotions for each consumer. Determining a product recommendation can later be used to determine a marketing strategy, the Apriori algorithm has a simple formula, namely by determining the value of support and confidence, support means the number of items purchased the most and confident is the calculation of an estimate with a percent value of the number of items purchased. The apirori algorithm can easily and precisely see the pattern of purchases of goods made by consumers and by category these goods can be displayed on the website's main page. These favorite products can be used as marketing media to promote the most purchased items as well as determine the stock of goods.